The Effect Of Profitability On Company Value In Property And Real Estate Companies Listed On The Indonesian Stock Exchange From 2020 To 2023: Pengaruh Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020 Sampai Dengan 2023 - Prastianto, Fayyadh Dzaky; Mulyani, Sri; Siti Ayu Rosida; Setiawati (OGZ Research & Publishing, 2025)
Abstract: The property and real estate sector plays an important role in the Indonesian economy, but the profitability and company value in this sector show fluctuating trends. Objective: This study aims to analyse the profitability, company value, and the effect of profitability on company value in property and real estate companies listed on the Indonesia Stock Exchange for the period 2020–2023. Methodology: This study uses a quantitative method with purposive sampling of 40 data points, using secondary data from financial reports, and analysed using simple linear regression through SPSS version 24. Research Findings: The analysis results show that profitability has an average value of 4.289 and average company value of 1.189, both of which show a positive trend. The regression test proves that profitability has a positive and significant effect on company value, with a coefficient of determination of 0.418. Keywords: Profitability, Firm Value, Real Estate